2012
DOI: 10.1111/1574-6941.12027
|View full text |Cite
|
Sign up to set email alerts
|

Composition, richness and nonrandom assembly of culturable bacterial-microfungal communities in floral nectar of Mediterranean plants

Abstract: The recent upsurge of interest in the role of floral nectar as a habitat for microorganisms has led to some detailed analyses of nectarivorous yeasts. In contrast, very little is known on the occurrence and diversity of nectar-dwelling bacteria, and bacterial-fungal interactions within nectar remain unexplored. In this work, we studied both the culturable bacteria and microfungi found in the floral nectar of wild Mediterranean plants. In general, bacteria and yeasts were found coexisting in nectar more often t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
100
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 72 publications
(131 reference statements)
6
100
2
1
Order By: Relevance
“…[54], [55]). In particular, we note that Álvarez-Pérez & Herrera [30] found bacteria in 2.6% of the nectar samples of A. aestivus , while we isolated bacteria from all the examined samples. We attribute this to the different culturing methods, since those authors [30], used the rich medium trypticase soy agar (TSA) without sucrose, while we employed R2A agar (which contains far fewer proteins) supplemented with 30% sucrose which better mimics the nectars' nutritional environment.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…[54], [55]). In particular, we note that Álvarez-Pérez & Herrera [30] found bacteria in 2.6% of the nectar samples of A. aestivus , while we isolated bacteria from all the examined samples. We attribute this to the different culturing methods, since those authors [30], used the rich medium trypticase soy agar (TSA) without sucrose, while we employed R2A agar (which contains far fewer proteins) supplemented with 30% sucrose which better mimics the nectars' nutritional environment.…”
Section: Discussionmentioning
confidence: 47%
“…Still, it may be that not all the Acinetobacter OTUs were identified by culture [28]. We identified 161 representative isolates, which is a relatively large number compared with the number in other studies on culture-dependent bacterial communities in nectar [28], [30], [35] and on nectar-dwelling yeasts (e.g. [54], [55]).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Firstly, bacteria were ๙ever detected i๙ our microscopical (×400 a๙d ×1000 mag๙ificatio๙) observatio๙s of both i๙oculated a๙d co๙trol samples. A๙d seco๙dly, prior culture-based assessme๙t of yeast a๙d bacteria abu๙-da๙ce i๙ H. foetidus a๙d R. officinalis has show๙ that, eve๙ whe๙ prese๙t, bacteria are ge๙erally a๙ u๙importa๙t compo๙e๙t of the microbial commu๙ities i๙ the ๙ectar of these species (Álvarez-Pérez & Herrera, 2013). Furthermore, the prese๙ce of yeasts other tha๙ M. reukaufii a๙d M. gruessii i๙ i๙oculated samples was too occasio๙al to have a๙y importa๙t effect o๙ our results.…”
Section: Discussionmentioning
confidence: 63%
“…Studies on microbial diversity conducted by Brysch-Herzberg (2004), Pozo, Herrera & Bazaga (2011), Álvarez Pérez & Herrera (2013), Jacquemyn et al (2013) and Mittelbach et al (2015) revealed that floral nectar is frequently colonized by specialized sugar-consuming yeasts in the Ascomycota and Basidiomycota phyla, along with several bacterial groups. However, most studies of nectar-living microorganisms have been conducted in temperate areas; knowledge of nectar microbial diversity in tropical habitats remains poor.…”
Section: Introductionmentioning
confidence: 99%